58.5k views
3 votes
Can u answer #19. I really need help. And PLEASE SHOW UR WORK!!!!!!!!!!!!

Can u answer #19. I really need help. And PLEASE SHOW UR WORK!!!!!!!!!!!!-example-1
User Mashawn
by
6.9k points

2 Answers

4 votes
p = m + n / -5
-5p = m + n ( because -5 was dividing with m + n so on an other side it will multiply )
-5p - m = n
User Daniel Barral
by
7.6k points
3 votes
Ok so first you would want to multiply both sides by -5.
P(-5)=(m+n/-5)-5 (So now do the multiplication)
-5p= m+n (You got rid of the -5 because -5 multiplied by -5 is 1 and if you put one under m+n, it would still not change) Now, isolate the n.
-5p-m=n < That would be your answer :)
I really hope this helped :)


User JWiley
by
7.2k points